New insights into the genetics and epigenetics of systemic sclerosis. Issue 11 (November 2018) - Angiolilli, Chiara; Marut, Wioleta; Kroef, Maarten; Chouri, Eleni; Reedquist, Kris; Radstake, Timothy
Abstract Systemic sclerosis (SSc) is a severe autoimmune disease that is characterized by vascular abnormalities, immunological alterations and fibrosis of the skin and internal organs. The results of genetic studies in patients with SSc have revealed statistically significant genetic associations with disease manifestations and progression. Nevertheless, genetic susceptibility to SSc is moderate, and the functional consequences of genetic associations remain only partially characterized. A current hypothesis is that, in genetically susceptible individuals, epigenetic modifications constitute the driving force for disease initiation. As epigenetic alterations can occur years before fibrosis appears, these changes could represent a potential link between inflammation and tissue fibrosis. Epigenetics is a fast-growing discipline, and a considerable number of important epigenetic studies in SSc have been published in the past few years that span histone post-translational modifications, DNA methylation, microRNAs and long non-coding RNAs. This Review describes the latest insights into genetic and epigenetic contributions to the pathogenesis of SSc and aims to provide an improved understanding of the molecular pathways that link inflammation and fibrosis. This knowledge will be of paramount importance for the development of medicines that are effective in treating or even reversing tissue fibrosis. Our ability to interrogate the genetic and epigenetic processes that underpin disease are advancing rapidly. In this Review, Radstake and colleagues highlight insights gained into the pathogenesis of systemic sclerosis from the past 4 years of genetic and epigenetic research. Key points Systemic sclerosis (SSc) is a complex fibrotic, autoimmune disease, the manifestations of which are only partially explained by genetic predisposition. The concordance rate for SSc in monozygotic twins is low, indicating that genetic predisposition is insufficient to explain disease development and suggesting a role for environmental factors and epigenetic influences. Epigenetic factors associated with SSc include changes in DNA methylation, histone modifications and the expression of microRNAs and long non-coding RNAs, which together drive aberrant immune activation and fibrosis. Integration of the knowledge derived from genomic and epigenomic studies in SSc is needed to improve the characterization of the disease. Therapies that target epigenetic pathways are emerging as promising therapeutic tools in experimental models of fibrosis, raising hope for future applications in SSc.